In situ immunogenic clearance induced by a combination of photodynamic therapy and rho-kinase inhibition sensitizes immune checkpoint blockade response to elicit systemic antitumor immunity against intraocular melanoma and its metastasis - In-San Kim (BMJ Publishing Group, 2021)
Background Uveal melanoma (UM) is the most frequent intraocular malignancy and is resistant to immunotherapy. Nearly 50% of patients with UM develop metastatic disease, and the overall survival outcome remains very poor. Therefore, a treatment regimen that simultaneously targets primary UM and prevents metastasis is needed. Here, we suggest an immunotherapeutic strategy for UM involving a combination of local photodynamic therapy (PDT), rho-kinase (ROCK) inhibitor, and PD-1/PD-L1 immune checkpoint blockade.Methods The antitumor efficacy and immune response of monotreatment or combinational treatment were evaluated in B16F10-bearing syngeneic mouse models. Abscopal antitumor immune responses induced by triple-combinational treatment were validated in syngeneic bilateral B16F10 models. After each treatment, the immune profiles and functional examinations were assessed in tumors and tumor draining lymph nodes by flow cytometry, ELISA, and immunofluorescence assays. In orthotopic intraocular melanoma models, the location of the immune infiltrate in the tumor microenvironment (TME) was evaluated after each treatment by multiplex immunohistochemistry and metastatic nodules were monitored.Results PDT with Ce6-embedded nanophotosensitizer (FIC-PDT) elicited immunogenic cell death and stimulated antigen-presenting cells. In situ immunogenic clearance induced by a combination of FIC-PDT with ripasudil, a clinically approved ROCK inhibitor, stimulated antigen-presenting cells, which in turn primed tumor-specific cytotoxic T cells. Moreover, local immunogenic clearance sensitized PD-1/PD-L1 immune checkpoint blockade responses to reconstruct the TME immune phenotypes of cold tumors into hot tumors, resulting in recruitment of robust cytotoxic CD8+ T cells in the TME, propagation of systemic antitumor immunity to mediate abscopal effects, and prolonged survival. In an immune-privileged orthotopic intraocular melanoma model, even low-dose FIC-PDT and ripasudil combined with anti-PD-L1 antibody reduced the primary tumor burden and prevented metastasis.Conclusions A combination of localized FIC-PDT and a ROCK inhibitor exerted a cancer vaccine-like function. Immunogenic clearance led to the trafficking of CD8+ T cells into the primary tumor site and sensitized the immune checkpoint blockade response to evoke systemic antitumor immunity to inhibit metastasis, one of the major challenges in UM therapy. Thus, immunogenic clearance induced by FIC-PDT and ROCK inhibitor combined with anti-PD-L1 antibody could be a potent immunotherapeutic strategy for UM.